The role of transient receptor potential channels in chronic kidney disease-mineral and bone disorder - Zhang, Lerong; Xu, Penghao; Hao, Lele; Wang, Lingling; Xu, Yunkai; Jiang, Chen (Frontiers in Pharmacology, 2025)
Chronic kidney disease (CKD) represents a major global health challenge, frequently resulting in the development of chronic kidney disease-mineral and bone disorder (CKD-MBD). Transient receptor potential (TRP) channels, particularly the TRPV (vanilloid), TRPC (canonical), and TRPM (melastatin) subfamilies, are crucial in CKD-MBD by regulating calcium homeostasis, bone remodeling, and vascular calcification. Pharmacological agents targeting TRP channels and traditional Chinese medicine therapies demonstrate promising therapeutic potential for CKD-MBD. This article explores the role of TRP channels in CKD-MBD, from molecular mechanisms to treatment prospects, aiming to provide new insights for CKD-MBD treatment.